Clinical Pattern of Pediatric Tuberculosis in a Tertiary Care Hospital in Bangladesh - Ahsan, Mohammed Rizwanul; Hussain, Manzoor; Makbul, Sabrina; Sarkar, Probir Kumar; Al Mamun, ABM Mahfuj Hasan (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Pediatric tuberculosis (TB) contribute a significant proportion of the TB burden in Bangladesh yet little is known about the clinical characteristics of this childhood TB which remains unclear. Objectives: This study of paediatric TB is designed to evaluate the clinical profile of childhood TB to determine the various clinical presentation of various type of childhood TB among the patients admitted in Dhaka Shishu(Children) Hospital. Methods: This is a cross-sectional retrospective study, we reviewed all case file of TB patients from January to June 2018 in the Division of Pediatrics medicine of Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh. Results: Among 51cases of tuberculosis most cases presented in the age between 1 to 5 years 21(41.18%), 7(13.73%) were within 1 year, 17(33.33%) were 6 to 10 years, 6(11.76%) were above 10 years of age. Most of them were male 27(52.94%) and 24(47.06%) were female. Maximum cases presented with symptoms of Fever 48(94.12%), Cough (84.31%), Vomiting 25(49.02%), Cold 36(70.59%), abdominal pain (18.8%), Breathlessness 12(23.53%), Convulsion 6(11.76%), lymphadenopathy 5 (16.13%), Swelling 4(7.84%) and Skin lesion 1(1.96%). Finally among all Tuberculosis cases most of them were Pulmonary TB 32(62.76%) and other forms of TB were abdominal TB 6(11.76%), CNS TB 5(9.80%), TB lymphadenitis 3(5.88%), miliary TB 2(3.92%), Disseminated TB 2(3.92%) and Tubercular abscess 1(1.96%). Conclusion: In this study pulmonary tuberculosis patients are more commonly found than extra-pulmonary tuberculosis in pediatric age group. DS (Child) H J 2019; 35(1) : 9-13